2022
DOI: 10.3390/life12020151
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Protein Levels Analysis in Multiple Sclerosis Sardinian Families Identified C9 and CYP24A1 as Candidate Biomarkers

Abstract: Here we investigate protein levels in 69 multiple sclerosis (MS) cases and 143 healthy controls (HC) from twenty Sardinian families to search for promising biomarkers in plasma. Using antibody suspension bead array technology, the plasma levels of 56 MS-related proteins were obtained. Differences between MS cases and HC were estimated using Linear Mixed Models or Linear Quantile Mixed Models. The proportion of proteins level variability, explained by a set of 119 MS-risk SNPs as to the literature, was also qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…Proteomic studies have shown a decrease in alpha-1-antichymotrypsin in the CSF of patients with RRMS compared with samples collected from patients with other inflammatory diseases of the CNS. This is supported by the results obtained in the validation of studies using ELISA in both sexes [14,21].…”
Section: Proteomasupporting
confidence: 70%
See 1 more Smart Citation
“…Proteomic studies have shown a decrease in alpha-1-antichymotrypsin in the CSF of patients with RRMS compared with samples collected from patients with other inflammatory diseases of the CNS. This is supported by the results obtained in the validation of studies using ELISA in both sexes [14,21].…”
Section: Proteomasupporting
confidence: 70%
“…However, the availability of leakage or release of products from different tissues or blood cells in the plasma may correspond with pathological and physiological condition of the specific tissues. Since that plasma is easy to be received in noninvasive way, it can be proposed as a useful fluid for deriving promising diagnostic biomarkers [14].…”
Section: Requirements For Ms Biomarkersmentioning
confidence: 99%
“…Specifically, as reported in [ 15 ], a bead-based antibody array format, containing human platelet antigen antibodies immobilized into microspheres in suspension, was used to profile proteins via direct labeling of whole and unfractionated samples with biotin. Antibody-conjugated bead arrays were analyzed in a multiplexed manner with immediate data acquisition from the flow cytometer-like Flexmap 3D instrument, to determine relative signal intensities from the binding of antibodies to their target antigens.…”
Section: Methodsmentioning
confidence: 99%
“… and were assumed to be independent. Sex and MS status were included in the model as fixed effects to avoid potential confounding [ 15 , 28 ]. Variance component decomposition was performed according to the total trait variance ( ) decomposition provided by the formula: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation